1989
DOI: 10.2151/jmsj1965.67.2_279
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Optical Characteristics in the Yellow Sand Events Observed in May, 1982 at Nagasaki-Part II Models

Abstract: Phase functions of yellow sand particles were measured by a polar nephelometer during 24 April-11 May, 1982 at Nagasaki, Japan. They suggested a strong nonsphericity of the particles, which can be reconstructed by the semi-empirical theory of Pollack and Cuzzi or by Mie particles with large fictitious absorption. Spectral extinction cross section, single scattering albedo, asymmetry factor and backscattering phase function were estimated using the volume spectra retrieved from data of several instruments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(88 citation statements)
references
References 24 publications
2
85
1
Order By: Relevance
“…With this in mind, the atmosphere was divided into two layers, above and below 4300 m, and were treated separately in the lidar data analysis. Nakajima et al (1989), by analyzing the angular scattering data from a polar-nephelometer, reported that S1 ranges from 49 to 87 for the Kosa event at Nagasaki. They also pointed out that the effect of non-sphericity of the Kosa particles causes relatively larger values of Sl in spite of consisting of low-absorptive soil particles.…”
Section: Results O F Analysismentioning
confidence: 99%
“…With this in mind, the atmosphere was divided into two layers, above and below 4300 m, and were treated separately in the lidar data analysis. Nakajima et al (1989), by analyzing the angular scattering data from a polar-nephelometer, reported that S1 ranges from 49 to 87 for the Kosa event at Nagasaki. They also pointed out that the effect of non-sphericity of the Kosa particles causes relatively larger values of Sl in spite of consisting of low-absorptive soil particles.…”
Section: Results O F Analysismentioning
confidence: 99%
“…Nakajima et al, 1989;Kuik, 1992] and composition of the aerosols. In particular, the differences in wavelength dependence observed for the individual samples may be a useful tool to distinguish between different types of irregular aerosols.…”
Section: Aerosol Measurementsmentioning
confidence: 99%
“…However, for the most part real aerosols are not spherical particles, and the non-sphericity may cause erroneous estimations of the size distribution and the com-plex refractive index (Asano and Sato,1980;Pollack and Cuzzi,1980;Kobayashi,1986b;Nakajima et al, 1989). Effects of non-sphericity on the retrieval of particle size distributions from aircraft radiative flux measurements have been investigated by Welch et al (1981).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…2b and also in Fig. 4 of Part I, and they 1 The aerosol optical thicknesses were computed from Mie theory for the size distribution that was estimated from the OPC-derived size distribution by extrapolating it to smaller radii down to 0.1*m and setting it constant for radii between 0.1 and 0.02*m. might be less absorbing for the visible light as yellow sand particles are (e.g., Nakajima et al, 1989). The corresponding optical thicknesses are shown in Fig.…”
Section: Estimation Of the Aerosol Size Distribution (A) Troposphericmentioning
confidence: 99%